Neuroimmunomodulation of vagus nerve stimulation and the therapeutic implications - Fang, Yi-Ting; Lin, Ye-Ting; Tseng, Wu-Lung; Tseng, Philip; Hua, Gia-Linh; Chao, Ying-Jui; Wu, Yi-Jen (Frontiers in Aging Neuroscience, 2023)
Vagus nerve stimulation (VNS) is a technology that provides electrical stimulation to the cervical vagus nerve and can be applied in the treatment of a wide variety of neuropsychiatric and systemic diseases. VNS exerts its effect by stimulating vagal afferent and efferent fibers, which project upward to the brainstem nuclei and the relayed circuits and downward to the internal organs to influence the autonomic, neuroendocrine, and neuroimmunology systems. The neuroimmunomodulation effect of VNS is mediated through the cholinergic anti-inflammatory pathway that regulates immune cells and decreases pro-inflammatory cytokines. Traditional and non-invasive VNS have Food and Drug Administration (FDA)-approved indications for patients with drug-refractory epilepsy, treatment-refractory major depressive disorders, and headaches. The number of clinical trials and translational studies that explore the therapeutic potentials and mechanisms of VNS is increasing. In this review, we first introduced the anatomical and physiological bases of the vagus nerve and the immunomodulating functions of VNS. We covered studies that investigated the mechanisms of VNS and its therapeutic implications for a spectrum of brain disorders and systemic diseases in the context of neuroimmunomodulation.